The state of scientific research of militia activity in Ukraine during the period of partial liberalisation of the political regime in the USSR (1953–1962) (Law and Safety, 2024)
The historiography of militia activity during the years of partial de-Stalinisation is divided into two stages: the Soviet period and the period of Ukraine’s independence. The 1960s-1980s were marked by a significant increase in researchers' interest in studying the general issues of the history and legal foundations of internal affairs. At that time, monographic studies and dissertations appeared, which dealt with various issues of theory and practice of organisation and functioning of militia bodies, including development and improvement of the structure, functions and legal basis of their activities, restructuring of the work of internal affairs bodies in accordance with the conditions of the “thaw”, organisation of combating crime, protection of public order, performance of managerial and economic tasks, and resolution of special issues. A significant part of the works covers the issues of party leadership of internal affairs bodies, they are presented exclusively within the framework of the traditional assessment of the activities of these institutions, i.e. their “praise and glorification”.The second period in militia history research is characterised by a theoretical rethinking of previous established historical ideas, a radical revision of the concepts that previously dominated historical and legal science. For the first time, specialists in the history of law enforcement agencies were able to conduct historical research free from ideological attitudes. Over the past decades, a number of works by foreign scholars have been published that examine some aspects of the role of law enforcement agencies during the period of Stalin's totalitarian regime. They analyse some of the causes of crime and its evolution in the USSR at that time, and examine the social and cultural impact of the Thaw on relations, decision-making and policy-making in the Soviet Union during the period when N. S. Khrushchev was its leader. Foreign scholars emphasise that many of the reform initiatives commonly associated with Khrushchev personally and with the period of his rule in general often have their roots in the Stalinist period, both in their content and in the way they were implemented.It has been stated that the activities of the militia in Ukraine in the 1950s and 1960s are insufficiently studied.
Keywords: Ukraine; 1950s–1960s; partial liberalisation of the political regime in the USSR; history of the state and law of Ukraine; Ministry of Internal Affairs; militia; historiography of the history of internal affairs bodies.